Effectiveness of Pearl NPK Fertilizer Application and Rabbit Urine POC Concentration on the Growth and Yield of Pagoda Mustard (Brassica narinosa L) - M. Arif Dzakiyul Fikri; Andriani Eko Prihatiningrum (Demeter: Journal of Farming and Agriculture, 2026)
Pagoda Cabbage (Brassica narinosa L), also known as Ta Ke Chai, is a type of horticultural vegetable with convex, circular leaves resembling blooming flowers, belonging to the Brassicaceae family. The objective of this study was to determine the combination dose of NPK Mutiara inorganic fertilizer and POC Rabbit Urine organic fertilizer that could provide the best growth and yield for Pagoda Mustard plants. This study was conducted in Sedayulawas Village, Brondong District, Lamongan Regency, East Java Province, from January to March 2025. The experimental method used was a 2-factor experimental method using a Randomized Block Design (RBD), with 16 treatments and 4 replications. The treatments consisted of the first factor of NPK Mutiara fertilizer application with the symbol A, namely: No NPK fertilizer, 50 ml NPK, 100 ml NPK, 150 ml NPK. The second factor was the application of POC Rabbit Urine with the symbol U, namely: 50 ml POC, 100 ml POC, 150 ml POC, 200 ml POC. The data were analyzed using analysis of variance and followed by BNJ, with the observation variables being plant height, number of leaves, leaf area, root length, wet weight, and dry weight. The results of this study indicate that the Rabbit Urine POC treatment has a significant effect on all observation variables of pagoda mustard plant growth and yield because the higher the concentration of Rabbit Urine POC given, the better the plant growth results. This shows that Rabbit Urine can supply nutrients in the soil because the higher the dose given, the greater the nutrient content received by the plants.